Economic contribution of agritourism in Zimbabwe: An empirical study - Baipai, Rudorwashe; Basera, Vitalis; Baipai, Richard; Kwinje, Catherine Paada; Hurombo, Brighton (Bahasa Indonesia, 2025)
Agritourism is an important economic driver that has contributed significantly to the economies of most developed countries. However, the significance of the contribution of agritourism has been minimally explored in the developing world context, particularly in Zimbabwe. Therefore, this study aims to assess the economic contribution of agritourism in Zimbabwe from the supply side. Using a qualitative approach, farmers' perceptions of the economic contributions of agritourism were collected and analyzed. The assessed variables included farm income, sales, profits, employment, tax revenue generated, value addition, size of agritourism businesses, and Gross Domestic Product (GDP). Twenty (21) agritourism ventures were purposively selected and in-depth interviews were conducted. The results of this study indicate that agritourism’s contribution to Zimbabwe's economy is still meager. They showed that agritourism activities increased farm income, sales, profits, employment, tax remittances, value addition, and GDP by a small margin. Revenue generated through farm entry fees and farm activities has a low effect on farm profits, except for farms with accommodation facilities. Therefore, the study recommends the development of various adaptable strategies to increase tourist flow to farms, including increased marketing efforts, offering family and holiday events, creating entertainment facilities, and increasing agricultural production. The results of this study provide policymakers, farmers, and other relevant stakeholders with information that can be used to assess the potential and profitability of agritourism. Furthermore, policy recommendations are provided to strengthen agritourism as a sustainable diversification strategy for farmers.